Two new species of Acanthocyrtus Handschin, 1925 (Collembola, Entomobryidae, Entomobryinae) from Western Australia - Cipola, Nikolas Gioia; Greenslade, Penelope (Zootaxa, 2022)
Two new species of Acanthocyrtus Handschin from Western Australia are described and illustrated here. Acanthocyrtus necropolitanus sp. nov. and A. pallidus sp. nov. resemble other congenerics by having smooth prelabral chaetae and a unique dorsal chaetotaxy pattern from the third thoracic segment to the third abdominal segment, but both new species are distinguished from others by the presence of labral papillae, a feature is revealed here for the first time in the genus. An identification key for all species in the genus is provided. The description of these two Acanthocyrtus species now increased from six to eight and is now known from southwestern Australia.